Progressive scale convolutional network for spatio-temporal downscaling of soil moisture: A case study over the Tibetan Plateau - Ziyu Zhou; Keyan Hu; Ling Zhang; Zhaohui Xue; Yutian Fang; Yusha Zheng (Journal of Hydrology, 2026)

Elevation dependence of vegetation phenology on the southeastern margin of the Tibetan Plateau - Tiantian Yang; Zheneng Hu; Wanxiong Zhang; Jingjing Wang; Zhongshi Zhang; Keyan Fang; Xin Zhou; Jie Zhou; Zhuoya Zhang; Zhengtang Guo (Science China Earth Sciences, 2026)

Enhanced remediation of residual DNAPL by ethanol cosolvent flushing: Mass transfer behavior and empirical correlation - Yingxue Hu; Keyan Wang; Chunwei Zhang; Tetsuya Suekane; Junwei Su; Zhaolin Gu (Journal of Hazardous Materials, 2026)

Drip irrigation combined with organic fertilizers improves crop N uptake and yield by reducing soil salinity and N loss in saline–alkali sunflower farmlands - Min Hu; Yue Li; Zhijun Chen; Keyan Lv; Yunwu Xiong; Guanhua Huang (Soil and Tillage Research, 2026)

Organic amendments promote sunflower nutrient uptake by recruiting stable beneficial microbiomes in saline–alkali farmland - Min Hu; Yue Li; Zhijun Chen; Keyan Lv; Yunwu Xiong; Guanhua Huang (Plant and Soil, 2025)

Innovation for mine reclamation: Improving the reclamation efficiency and cropland rate in mining subsidence areas - Gensheng Li; Keyan Guo; Zhenqi Hu; Zhuo Wang; Wenjuan Wang; Yaokun Fu; Jinmao Ju; Junhui Zhang (Journal of Cleaner Production, 2025)

Overexpression of long non‑coding RNA H19 enhances cell viability and inhibits apoptosis in recurrent spontaneous abortion by targeting the miR-29a-3p/SOCS3 axis - Zhengli Qian; Keyan Luo; Mingzhe Zhang; Dejing Wang; Yu Hu; Qinghan Li (In Vitro Cellular & Developmental Biology - Animal, 2025)

An improved method for extracting cellulose from fossil wood and its paleoclimatic implications - Donghao Wu; Xin Wang; Yang Deng; Mi Wang; Gang Hu; Xuan Ding; Linlin Gao; Keyan Fang; Xiaohua Gou (Frontiers of Earth Science, 2025)

The biodegradation pathway of HBCDs in the enriched microbial community - Bing Zhang; Wenqi Luo; Yongjin Liu; Haonan Chen; Tiantian Pan; Baole Wang; Keyan Li; Huaqing Jia; Shirou Zhou; Shanshan Meng; Xueying Ye; Tao Peng; et al. (International Biodeterioration & Biodegradation, 2025)

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Importance of forest stand structures for gross rainfall partitioning on China’s Loess Plateau - Xu Hu; Zhaoqi Fu; Ge Sun; Biao Wang; Keyan Liu; Churui Zhang; Lu Han; Lixin Chen; Zhiqiang Zhang (Journal of Hydrology, 2024)

Reconstruction of seasonal precipitation anomalies from tree-ring latewood records in southeastern China - Xinguang Cao; Pei-ken Kao; Hongbing Hu; Feifei Zhou; Di Zhang; Keyan Fang (Climate Dynamics, 2024)

Recovery of bio‑sulfur and metal resources from mine wastewater by sulfide biological oxidation-alkali flocculation: A pilot-scale study - Xin Hu; Hong Yang; Xiaoyue Fang; Tongyu Shi; Keyan Tan (Science of The Total Environment, 2023)

Improved spring temperature reconstruction using earlywood blue intensity in southeastern China - Xinguang Cao; Hongbing Hu; Pei‐ken Kao; Brendan M. Buckley; Zhipeng Dong; Xiuling Chen; Feifei Zhou; Keyan Fang (International Journal of Climatology, 2022)
Because instrumental observations are too short to fully represent long‐term natural variability, high‐resolution temperature proxy records are essential to understanding past climate and assessing current climate variability in the context of long‐term patterns. In the subtropics, progress in this field has been hampered by a relative lack of long and truly temperature‐sensitive proxy records. In this study, we provide an assessment of the dendroclimatic potential of blue intensity (BI) and ring‐width (RW) measurements from two hot/humid Pinus massoniana sites in China. Our results show that RW exhibits a significant ( p

Biodegradable chitosan-ethylene glycol hydrogel effectively adsorbs nitrate in water - Changhong Chen; Yiwei Guo; Li Long; Keyan Chen; Xiaolan Hu; Yingwen Xue (Environmental Science and Pollution Research, 2020)

Is APOE $\boldsymbol{ε}$ 3 a favourable factor for the longevity: an association study in Chinese population - JIE FENG; LEI XIANG; GANG WAN; KEYAN QI; LIANG SUN; ZEZHI HUANG; CHENGUANG ZHENG; ZEPING LV; CAIYOU HU; ZE YANG (Journal of Genetics, 2011)